2018
DOI: 10.1111/lam.13103
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ureolytic bacteria with calcifying abilities isolated from limestone caves for biocalcification

Abstract: Biocalcification through the use of ureolytic bacteria and biochemical activities has evolved in recent decades into a fervent resourceful effective technology suitable for soil stabilization, crack repair and bioremediation. Extensive studies have been carried out on numerous ureolytic bacterial species isolated from soils and sewage samples. However, very limited attention has been given to limestone caves with natural calcite formations as a possible source for isolation of ureolytic bacteria. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…Similar to our results many bacterial strains including Bacillus and Pseudomonas with high enzyme activities showed high CaCO3 precipitation [33]. Omoregie et al [22] reported that urease activities for the bacteria isolated from limestone caves had higher urease activity. In addition, Sun et al [21] emphasized that the urease activity of B. megaterium was lower than that of S. pasteurii at high temperatures such as 25 °C and 30 °C.…”
Section: Enzymes Activitiessupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our results many bacterial strains including Bacillus and Pseudomonas with high enzyme activities showed high CaCO3 precipitation [33]. Omoregie et al [22] reported that urease activities for the bacteria isolated from limestone caves had higher urease activity. In addition, Sun et al [21] emphasized that the urease activity of B. megaterium was lower than that of S. pasteurii at high temperatures such as 25 °C and 30 °C.…”
Section: Enzymes Activitiessupporting
confidence: 91%
“…Also these results were parallel to our results. On the other hand, there are no correlation between urease activity and bio-calcification [22]. Besides these, Bacillus aerius U2 achieved maximum calcium carbonate precipitate at the end of a longer incubation (14 days) compared to S. pasteurii ATCC 6453 (7 days).…”
Section: Calcium Carbonate Precipitationmentioning
confidence: 90%
“…As the growth remains stationary and pH further increased to >8.2, urease activities were at least 253 U ml -1 in all the cultures. Urease activities observed in this report were assumedly the rst at acidic pH, which compared favourably with values recorded at alkaline pH in previous studies [7,16,41,43]. Moreover, pH of the culture system kept increasing, alleviating the acidity condition that initially prevailed in the AMD system.…”
Section: Alpha Diversity and Phylogeny Of Microbial Otus In Amd From supporting
confidence: 87%
“…The bacteria (particularly Acinetobacter pittii, Pseudomonas citronellolis, and Bacillus cereus) have been involved in degradation of indole, a heterocyclic aromatic compound found in coal, via attack on either/or both the carbocyclic and N-heterocyclic rings [37]. Studies involving Acinetobacter [38], Enterobacteriaceae [39], Pseudomonas [40], Sporosarcina [7,41], Bacillus [41], and Exiguobacterium [38] OTUs for sequestration of toxic metals/metalloids in environmental media have been reported. Bioaccumulations of Cd, Co, and Zn were reported for Sporosarcina sp.…”
Section: Alpha Diversity and Phylogeny Of Microbial Otus In Amd From mentioning
confidence: 99%
“…These microorganisms were determined to be used in the construction of bio-concretes, crack healing in concretes, and soil bioremediation. In addition, diverse enzyme activities revealed in cave isolates can serve industrial uses with low energy spending [11,22,24,25]. Wastes bioremediation potentials were detected also in cave isolates [5,25].…”
Section: The Dominance Of Bacterial Group Belonging To Epsilonproteobmentioning
confidence: 95%